2015
DOI: 10.1007/s11590-015-0852-0
|View full text |Cite
|
Sign up to set email alerts
|

OMEGA one multi ethnic genetic approach

Abstract: The genetic algorithm (GA) is a quite efficient paradigm to solve several optimization problems. It is substantially a search technique that uses an ever-changing neighborhood structure related to a population which evolves according to a number of genetic operators. In the GA framework many techniques have been devised to escape from a local optimum when the algorithm fails in locating the global one. To this aim we present a variant of the GA which we call OMEGA (One Multi Ethnic Genetic Approach). The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…In this section, we compare the performances of the three proposed heuristic approaches on a set of benchmark instances. In order to generate test cases, we started from a dataset used in previous works for the base MLST problem . The instances that we considered are randomly generated graphs having a number of nodes ∣ V ∣ equal to 20, 30, 40, 50, 100, or 200, a number of labels ∣ L ∣ equal to the number of nodes, and a number of edges ∣ E ∣ equal to dVV12, where d is a density measure equal to 0.2, 0.5, or 0.8.…”
Section: Computational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we compare the performances of the three proposed heuristic approaches on a set of benchmark instances. In order to generate test cases, we started from a dataset used in previous works for the base MLST problem . The instances that we considered are randomly generated graphs having a number of nodes ∣ V ∣ equal to 20, 30, 40, 50, 100, or 200, a number of labels ∣ L ∣ equal to the number of nodes, and a number of edges ∣ E ∣ equal to dVV12, where d is a density measure equal to 0.2, 0.5, or 0.8.…”
Section: Computational Resultsmentioning
confidence: 99%
“…The authors also showed this new bound to be tight. Metaheuristics for the problem were proposed in several works . In , the authors presented a single‐commodity flow mathematical model, and showed that the formulation obtained by relaxing integrality on the arc selection variables always provides the optimal solution value for the original unrelaxed problem.…”
Section: Introductionmentioning
confidence: 99%
“…The Mega is a technique developed for the GAs which is aimed at reducing the probability of remaining trapped at a local minimum [4]. The main idea behind the algorithm is to split a starting population in k different subpopulations that, independently, evolve in k different environments.…”
Section: Multiethnic Genetic Approachmentioning
confidence: 99%
“…Actually, the idea of allowing the simultaneously evolve of k different populations was already adopted in parallel GAs as the Island Model (see [12,19]). However, in Mega each population is characterized by its own fitness function that is appropriately selected to diversify the evolution and to carry out a better exploration of the solution space (for more details see [4]).…”
Section: Multiethnic Genetic Approachmentioning
confidence: 99%
“…• The paper [6] written by Cerrone, Cerulli, and Gaudioso presents a genetic algorithm called by the authors OMEGA (One Multi Ethnic Genetic Approach). The main difference with respect to existing genetic methods is that, starting from an initial population, k different sub-populations are produced at each iteration and they independently evolve in k different environments.…”
mentioning
confidence: 99%